Analysis of Workbench Flatness Measurement and Product Result of 3 Axis CNC Router Machine - Junaidi, Abdul Khair; Mendofa, Dyon Shaputra; Arief, Dodi Sofyan (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
The development of technology in the industrial sector is increasing rapidly, especially the application of computers in the field of machinery. Demands from consumers who want good quality workpieces, precision, completed in a short time and in large quantities, will be easier to work with a CNC Router machine. Surface flatness is an absolute thing that must be considered in the machining process, especially the 3 Axis CNC Router machine. This type of research is an experimental research, using Dutch teak wood as a workpiece with a height of 15 mm, a length of 100 mm and a width of 80 mm, the machining process uses a 3 Axis CNC Router Machine. The flatness of the workbench is first measured, then the product is prepared with a depth of 2 mm in the product area. The research uses a variation of the spindle speed of 600 rpm, 800 rpm and 1000 rpm. After that, measurements are taken to obtain the flatness value. Measuring flatness using a Dial indicator measuring instrument with accuracy (1 µm). The best product flatness test or the lowest value is (32.00 µm) obtained from the spindle speed of 1000 rpm and the most uneven product evenness is (56.00 µm) obtained from the spindle speed of 600 rpm, knowing the effect of the flatness value of the workbench on the product flatness value 3 Axis CNC Router Machine, that the flatter the workbench, the flatter the product results. The results of the research can be used to refine machining strategies to achieve optimal machining.